2009
DOI: 10.1016/j.nimb.2009.05.051
|View full text |Cite
|
Sign up to set email alerts
|

Competition of terrace and step-edge sputtering under oblique-incidence ion impact on a stepped Pt(111) surface

Abstract: a b s t r a c tUsing molecular-dynamics simulation, we study the sputtering of a Pt(1 1 1) surface under oblique and glancing incidence 5 keV Ar ions. For incidence angles larger than a critical angle # c , the projectile is reflected off the surface and the sputter yield is zero. We discuss the azimuth dependence of the critical angle # c with the help of the surface corrugation felt by the impinging ion. If a step exists on the surface, sputtering occurs also for glancing incidence # > # c . We demonstrate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In previous work, 7,8,23,24 we determined that ions interact with the step-and can enter a subsurface channel-only if their impact point is within a region −x c < ξ < 0; that is, not farther than the critical distance x c away from the step edge. For a flat terrace, x c is given by a simple geometrical criterion, 25…”
Section: The 110 Channelsmentioning
confidence: 99%
“…In previous work, 7,8,23,24 we determined that ions interact with the step-and can enter a subsurface channel-only if their impact point is within a region −x c < ξ < 0; that is, not farther than the critical distance x c away from the step edge. For a flat terrace, x c is given by a simple geometrical criterion, 25…”
Section: The 110 Channelsmentioning
confidence: 99%
“…The cases of a single isolated adatom ͑N =1͒ and of a densepacked surface step ͑corresponding to N = ϱ͒ have been simulated previously. [1][2][3][4]6,10,21 The adatoms are put on stable fcc sites on top of the crystallite. The island position, as well as that of all surface atoms are relaxed.…”
Section: A Simulationsmentioning
confidence: 99%
“…The effect of surface steps has been analyzed in detail. [1][2][3][4] It was shown that if the ion impact point is in the vicinity of an ascending step edge, an ion may sputter as many atoms as for normal incidence. The sputter yield of a stepped surface is thus primarily governed by the step density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation